ADPedKD: A Global Online Platform on the Management of Children With ADPKD - ALPAY, HARİKA; GÖKCE, İBRAHİM (ELSEVIER SCIENCE INC, 2019)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common monogenic cause of renal failure. For several decades, ADPKD was regarded as an adult-onset disease. In the past decade, it has become more widely appreciated that the disease course begins in childhood. However, evidence-based guidelines on how to manage and approach children diagnosed with or at risk of ADPKD are lacking. Also, scoring systems to stratify patients into risk categories have been established only for adults. Overall, there are insufficient data on the clinical course during childhood. We therefore initiated the global ADPedKD project to establish a large international pediatric ADPKD cohort for deep characterization. Methods: Global ADPedKD is an international multicenter observational study focusing on childhood-diagnosed ADPKD. This collaborative project is based on interoperable Web-based databases, comprising 7 regional and independent but uniformly organized chapters, namely Africa, Asia, Australia, Europe, North America, South America, and the United Kingdom. In the database, a detailed basic data questionnaire, including genetics, is used in combination with data entry from follow-up visits, to provide both retrospective and prospective longitudinal data on clinical, radiologic, and laboratory findings, as well as therapeutic interventions. Discussion: The global ADPedKD initiative aims to characterize in detail the most extensive international pediatric ADPKD cohort reported to date, providing evidence for the development of unified diagnostic, follow-up, and treatment recommendations regarding modifiable disease factors. Moreover, this registry will serve as a platform for the development of clinical and/or biochemical markers predicting the risk of early and progressive disease.
Keywords: ADPKD; ADPedKD Registry; children; longitudinal; DOMINANT POLYCYSTIC KIDNEY; RENAL CONCENTRATING CAPACITY; LEFT-VENTRICULAR MASS; BLOOD-PRESSURE; CARDIOVASCULAR-ABNORMALITIES; DISEASE ADPKD; PROGRESSION; VOLUME; CHILDHOOD; SPECTRUM